COMPENSATION SYSTEM OF WAQF LAND ACQUIRED FOR DEVELOPING PUBLIC INTEREST - Rofi Wahanisa; Suhadi Suhadi; Aprila Niravita (Fakultas Hukum, Universitas Diponegoro, 2022)
A number of activities related to land acquisition for public interest use waqf. The principle of waqf is derived from Islamic Law in which wakif (the owner) donates waqf (in the form of land) to nazhir (the manager of the edified property) for worship purposes. The problems in this paper consist of whether there is a system regarding waqf land acquired for public interest, and how compensation and supervision are given regarding waqf land acquired for developing public interest. Using normative legal research with legislation and conceptual approach, this paper argues that acquisition of waqf land is regulated in Law No. 2/2012 on Land Acquisition for Developing Public Interest and Law No. 41/2004 on Waqf. it is regulated that compensation will be given to nazhir for waqf land acquired. It also regulates that the status of waqf land can be changed into non-waqf one for public interest through exchange mechanism. In order to provide legal certainty over waqf land acquired for public interest, legislation on land acquisition needs to be harmonized with legislation on waqf.